A Large-Scale Computational Analysis of Corneal Structural Response and Ectasia Risk in Myopic Laser Refractive Surgery - Dupps, Jr, William Joseph; Seven, Ibrahim (Transactions of the American Ophthalmological Society, 2016)
To investigate biomechanical strain as a structural susceptibility metric for corneal ectasia in a large-scale computational trial. A finite element modeling study was performed using retrospective Scheimpflug tomography data from 40 eyes of 40 patients. LASIK and PRK were simulated with varied myopic ablation profiles and flap thickness parameters across eyes from LASIK candidates, patients disqualified for LASIK, subjects with atypical topography, and keratoconus subjects in 280 simulations. Finite element analysis output was then interrogated to extract several risk and outcome variables. We tested the hypothesis that strain is greater in known at-risk eyes than in normal eyes, evaluated the ability of a candidate strain variable to differentiate eyes that were empirically disqualified as LASIK candidates, and compared the performance of common risk variables as predictors of this novel susceptibility marker across multiple virtual subjects and surgeries. A candidate susceptibility metric that expressed mean strains across the anterior residual stromal bed was significantly higher in eyes with confirmed ectatic predisposition in preoperative and all postoperative cases (P≤.003). The strain metric was effective at differentiating normal and at-risk eyes (area under receiver operating characteristic curve ≥ 0.83, P≤.002), was highly correlated to thickness-based risk metrics (as high as R(2) = 95%, P<.001 for the percent of stromal tissue altered (PSTA)), and predicted large portions of the variance in predicted refractive response to surgery (R(2) = 57%, P<.001). This study represents the first large-scale 3-dimensional structural analysis of ectasia risk and provides a novel biomechanical construct for expressing structural risk in refractive surgery. Mechanical strain is an effective marker of known ectasia risk and correlates to predicted refractive error after myopic photoablative surgery.